Software Piracy: The Effects of Neutralization and Religiosity - Sikolia, David; Bahr, Gabriel; Biros, David (Journal of the Southern Association for Information Systems, 2025)
Software piracy poses a significant challenge with both economic and ethical implications. This study examines the influence of neutralization techniques and religiosity—encompassing both intrinsic and extrinsic dimensions—on the intention to engage in software piracy. Employing robust structural equation modeling (SEM), we analyzed survey data collected from 338 undergraduate business students in the United States. The findings indicate that neutralization techniques, specifically condemning the condemners, appealing to higher loyalties, and utilizing the ledger metaphor, serve as predictors of piracy intentions, suggesting that individuals are inclined to use cognitive rationalizations to justify their engagement in piracy. Additionally, intrinsic religiosity exhibited a negative correlation with piracy intention, implying a protective effect attributed to internalized moral values. Conversely, extrinsic religiosity demonstrated a positive correlation with piracy intention, suggesting that participation in external religious activities may be associated with ethical justifications for piracy. Furthermore, gender and age emerged as significant factors, with female participants and older individuals displaying lower intentions to engage in piracy. These results contribute to the literature on digital piracy by integrating concepts from religiosity and neutralization theory.